A Review of Mental Health and Mental Health Care Disparities Research: 2011-2014. (December 2019) - Cook, Benjamin Lê; Hou, Sherry Shu-Yeu; Lee-Tauler, Su Yeon; Progovac, Ana Maria; Samson, Frank; Sanchez, Maria Jose
Racial/ethnic minorities in the United States are more likely than Whites to have severe and persistent mental disorders and less likely to access mental health care. This comprehensive review evaluates studies of mental health and mental health care disparities funded by the National Institute of Mental Health (NIMH) to provide a benchmark for the 2015 NIMH revised strategic plan. A total of 615 articles were categorized into five pathways underlying mental health care and three pathways underlying mental health disparities. Identified studies demonstrate that socioeconomic mechanisms and demographic moderators of disparities in mental health status and treatment are well described, as are treatment options that support diverse patient needs. In contrast, there is a need for studies that focus on community- and policy-level predictors of mental health care disparities, link discrimination- and trauma-induced neurobiological pathways to disparities in mental illness, assess the cost effectiveness of disparities reduction programs, and scale up culturally adapted interventions.